KONFLIK ANTARA TUNTUTAN KERJA DAN KELUARGA SERTA PENGARUHNYA TERHADAP MOTIVASI KERJA PERSONIL PDKB (Pekerjaan Dalam Keadaan Bertegangan) - Pratesa, Dimas Putri Mega; Zahroh Anfi, Dieva; Sumarsetio, Yoga; Rahma, Adelia (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2025)
This study investigates the influence of work-family conflict on work motivation among employees of the PT Energized Electrical Work (PDKB) team. PLN Persero Malang. Employing a quantitative method with a census technique, all married male PDKB employees aged 27-36 served as respondents. Data were collected via questionnaires and analyzed using simple linear regression. The results indicate that work-family conflict does not significantly impact work motivation (R=0.274, R²=0.075; F-statistic=0.813, significance=0.389). Work-family conflict only explains 7.5% of the variation in work motivation, while other factors influence the remaining 92.5%. These findings suggest that in high-risk technical professions like PDKB, the relationship between work-family conflict and work motivation may be more complex, potentially mediated by coping mechanisms, social support, and job characteristics.